A novel vaccine formulation candidate based on lipooligosaccharides and pertussis toxin against Bordetella pertussis - Gao, Jingjing; Huang, Linlin; Luo, Shuquan; Qiao, Ruijie; Liu, Fanglei; Li, Xin (Frontiers in Immunology, 2023)
Pertussis is a severe human respiratory tract infectious disease caused by Bordetella pertussis that primarily affects infants and young children. However, the acellular pertussis vaccine currently administered can induce antibody and Th2 immune responses but fails to prevent the nasal colonization and transmission of B. pertussis, causing a resurgence of pertussis, so improved pertussis vaccines are urgently needed. In this study, we created a two-component pertussis vaccine candidate containing a conjugate prepared from oligosaccharides and pertussis toxin. After demonstrating the ability of the vaccine to induce a mixed Th1/Th2/Th17 profile in a mouse model, the strong in vitro bactericidal activity and IgG response of the vaccine were further demonstrated. In addition, the vaccine candidate further induced efficient prophylactic effects against B. pertussis in a mouse aerosol infection model. In summary, the vaccine candidate in this paper induces antibodies with bactericidal activity to provide high protection, shorten the duration of bacterial existence, and further reduce disease outbreaks. Therefore, the vaccine has the potential to be the next generation of pertussis vaccines.